2015
DOI: 10.1038/ajg.2015.120
|View full text |Cite
|
Sign up to set email alerts
|

C-Reactive Protein, Fecal Calprotectin, and Stool Lactoferrin for Detection of Endoscopic Activity in Symptomatic Inflammatory Bowel Disease Patients: A Systematic Review and Meta-Analysis

Abstract: Although CRP, FC, and SL are useful biomarkers, their value in managing individual patients must be considered in specific clinical contexts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
397
0
19

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 528 publications
(431 citation statements)
references
References 71 publications
15
397
0
19
Order By: Relevance
“…Along these lines, Lin et al (20) published a meta-analysis on FC accuracy in order to detect endoscopic activity, and Mosli et al (4) have recently published a meta-analysis on the accuracy of C-reactive protein, FC and fecal lactoferrin to detect endoscopic activity in IBD patients. Both studies observed considerable heterogeneity between the various tests due to a lack of diagnostic methodology standardization as there are so few studies evaluating endoscopic activity.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Along these lines, Lin et al (20) published a meta-analysis on FC accuracy in order to detect endoscopic activity, and Mosli et al (4) have recently published a meta-analysis on the accuracy of C-reactive protein, FC and fecal lactoferrin to detect endoscopic activity in IBD patients. Both studies observed considerable heterogeneity between the various tests due to a lack of diagnostic methodology standardization as there are so few studies evaluating endoscopic activity.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, the cut-off point is still not clearly defined for mucosal healing although some recent studies have opted for SES-CD ≤ 2 (9,10). If we also consider that colonoscopy for monitoring inflammatory activity can be complicated, then it is appropriate to identify and develop non-invasive biomarkers by producing evidence that shows that fecal biomarkers, in particular fecal calprotectin (FC), are a more accurate tool for predicting inflammatory activity in CD than blood tests (4). Such biomarkers include M2 pyruvate kinase (M2-PK), an enzyme that is expressed by continually replicating cells, such as intestinal mucus cells.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, fecal calprotectin is often used as a surrogate marker to assess disease activity in our outpatient clinic as it has been shown that there is a high correlation between fecal calprotectin and endoscopic disease activity in IBD patients. [72,103] The ultimate goal of all these strategies is to discontinue ineffective or unnecessary treatment, improve treatment efficacy and reduce side-effects of anti-TNF therapy.…”
Section: Expert Commentarymentioning
confidence: 99%